Culture and Isolation of Melanoma‐Initiating Cells. (1st February 2013) - Stecca, Barbara; Santini, Roberta; Pandolfi, Silvia; Penachioni, Junia Y.
Abstract: Melanoma is the most aggressive skin cancer. This unit illustrates protocols for culture and isolation of human melanoma cancer stem cells/tumor‐initiating cells (CSC/TIC). We describe two complementary methods to enrich for melanoma CSC/TIC. The first approach exploits the ability of CSC/TIC to grow as tumor spheres in low‐adherent culture conditions, as previously shown for neural stem cells and human embryonic stem cells. As a second approach, melanoma CSC/TIC are enriched by fluorescence‐activated cell sorting for the aldehyde dehydrogenase (ALDH) enzyme activity. We previously showed that melanoma cells with high ALDH activity (ALDH high ) are endowed with higher self‐renewal and tumorigenic abilities than the population with low activity (ALDH low ), suggesting that ALDH might be a good marker to select for melanoma CSC/TIC. This unit will also describe how to functionally test melanoma CSC/TIC by determining self‐renewal in vitro and tumor‐forming abilities in vivo using orthotopic xenograft assay. Curr. Protoc. Stem Cell Biol . 24:3.6.1‐3.6.12. © 2013 by John Wiley & Sons, Inc.